Technology adoption vs. continuous usage intention: Do decision criteria change when using a technology? - Kupfer, Anna; Ableitner, Liliane; Schöb, Samuel; Tiefenbeck, Verena (Americas Conference on Information Systems (AMCIS 2016), 2016)
Various models in Information Systems (IS) research seek to understand why individuals embrace or resist the adoption or use of a technology. Different models analyze the factors shaping user intentions at different stages of technology adoption and use. Yet, less is known how the factors shaping adoption intention subsequently evolve into continuous usage intention as users become (more) familiar with the technology. This paper investigates participants’ (N=549) adoption and continuous usage intention of a smartphone application for energy efficiency twice: at two different stages of experience, but for the same technology, in the same setting, and in particular with the same sample. In both cases, we use the Unified Theory of Acceptance and Use of Technology (UTAUT1&2). While UTAUT explains adoption intention well, we find only moderate support for continuous usage intention. In line with prior research, our data suggests that beliefs are updated from adoption to continuous usage stage.<br